University Student Organization Program at the Department Level and Fulfillment of Students' Social Needs - Dewi Aprillia; Faridah; Ahmad Restani Syukron Thayyib (Universitas Negeri Surabaya, 2026)
This study seeks to ascertain students’ perceptions of the relevance of student organization work programs at the departmental level to the fulfillment of students’ social relationship needs within the Department of Educational Administration, Faculty of Education, Universitas Negeri Makassar. The significance of this research lies in the pivotal role that student organizations play in supporting sustainable human resource development in higher education through the fulfillment of students’ social needs. This study draws upon Clayton Alderfer’s Existence, Relatedness, and Growth (ERG) Theory, with a specific focus on the dimension of social relationship needs (relatedness). Employing a quantitative descriptive approach, data were collected through online questionnaires distributed to 211 students. The data underwent descriptive statistical analysis. The findings reveal that student organization work programs, such as art and sports performances, basic student leadership training, and community service activities, have effectively fulfilled students’ social relationship needs. These programs foster teamwork, enhance effective communication, and cultivate a sense of belonging among students. Consequently, the study suggests that student organization work programs can serve as a sustainable platform for the development of students’ social competencies and the strengthening of social cohesion within higher education institutions.